Loss of Function of WFS1 Causes ER Stress-Mediated Inflammation in Pancreatic Beta-Cells - Morikawa, Shuntaro; Blacher, Lindsey; Onwumere, Chinyere; Urano, Fumihiko (Frontiers in Endocrinology, 2022)
Wolfram syndrome is a rare genetic disorder characterized by juvenile-onset diabetes mellitus, optic nerve atrophy, hearing loss, diabetes insipidus, and progressive neurodegeneration. Pathogenic variants in the WFS1 gene are the main causes of Wolfram syndrome. WFS1 encodes a transmembrane protein localized to the endoplasmic reticulum (ER) and regulates the unfolded protein response (UPR). Loss of function of WFS1 leads to dysregulation of insulin production and secretion, ER calcium depletion, and cytosolic calpains activation, resulting in activation of apoptotic cascades. Although the terminal UPR has been shown to induce inflammation that accelerates pancreatic β-cell dysfunction and death in diabetes, the contribution of pancreatic β-cell inflammation to the development of diabetes in Wolfram syndrome has not been fully understood. Here we show that WFS1-deficiency enhances the gene expression of pro-inflammatory cytokines and chemokines, leading to cytokine-induced ER-stress and cell death in pancreatic β-cells. PERK and IRE1α pathways mediate high glucose-induced inflammation in a β-cell model of Wolfram syndrome. M1-macrophage infiltration and hypervascularization are seen in the pancreatic islets of Wfs1 whole-body knockout mice, demonstrating that WFS1 regulates anti-inflammatory responses in pancreatic β-cells. Our results indicate that inflammation plays an essential role in the progression of β-cell death and diabetes in Wolfram syndrome. The pathways involved in ER stress-mediated inflammation provide potential therapeutic targets for the treatment of Wolfram syndrome.